Identification of slow rusters in bread wheat genotypes - Patidar, Rajesh Kumar; Kalappanavar, Ishwar Kenchappa; Kulkarni, Srikant (Journal of Cereal Research, 2012)
Genotypes HD-2189, HW-2021 showed the typical characteristics of slow rusters. These genotypes recorded low ACI, low AUDPC, considerable more latent period, medium pustule size and density and less rate of infection with good quantity of yield per hectare. However, genotypes DWR-195, DWR-162 and MACS-2496 recorded maximum ACI and relevant adverse values compared to slow leaf rusting genotypes and identified as fast rusters.